2020
DOI: 10.1108/gkmc-03-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the credibility of Web information by university students: findings from a case study in Iran

Abstract: Purpose The purpose of this paper is to explore how university students assess the credibility of diverse information available on the Web. Design/methodology/approach This paper used applied study and was conducted using the survey-descriptive method. Using a randomized stratified sampling method and the Cochran sampling formula, a sample including 380 student participants was selected from Shahid Beheshti University, Tehran, Iran. Data were gathered by administrating a validated questionnaire including eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(97 reference statements)
0
4
1
Order By: Relevance
“…Furthermore, the participants rated highly about the authority of information sources and the responsibility for information provided on e-government websites. This is in contrast to the finding by Keshavarz (2020), who found that students gave less attention to authority and source in comparison to semantic features. The respondents in this study perceived that the information provided on the e-government websites of Bangladesh are easy and clear in terms of understandability of the content.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the participants rated highly about the authority of information sources and the responsibility for information provided on e-government websites. This is in contrast to the finding by Keshavarz (2020), who found that students gave less attention to authority and source in comparison to semantic features. The respondents in this study perceived that the information provided on the e-government websites of Bangladesh are easy and clear in terms of understandability of the content.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, reputation of e-government websites creates trustworthiness among users regarding making references to relevant agencies of the government (Huang and Benyoucef, 2014). The accuracy of information had a high impact on the credibility of the websites which is considered as an important dimension for information quality assessment (Keshavarz, 2020). The respondents of this current study highly rated the credibility of e-government websites in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hicks (2021) argues that this inoculation metaphor characterises individuals as passive and vulnerable rather than being able to actively resist or contest messages. This chimes with other researchers who voice concerns that previous research into these specific forms of misinformation associated with conspiracy theory and extremism ideation in particular have not investigated people's ability to actively process information in order to promote analytical thinking (Douglas et al, 2019) such as making credibility judgements about websites (Keshavarz, 2020). Whitworth (2020a, p.25) regards information literacy as a potential solution, being in-itself a political act, 'enmeshed in formal and informal decision-making'.…”
Section: Misinformation Disinformation and Related Phenomenamentioning
confidence: 66%
“…However, there is a nuanced and highly statistically significant pattern, high-level information discerners are far more likely to strongly disagree with the statement than low discerners. This lack of critical awareness to make credibility judgements (Keshavarz, 2020) could make low-level information discerners vulnerable to misinformation of any material whether it be health related, extremist or conspiracy forming information as noted by Douglas et al (2019). In a linked statement regarding the authority of sources participants there was a marked difference in their responses.…”
Section: Discussionmentioning
confidence: 99%
“…Human credibility assessments of web content are often linked to surface signals. Indeed, website appearance, usability and design have frequently been shown to correlate with credibility [24]. We focus on the content and language of web pages rather than surface characteristics for multiple reasons.…”
Section: Signal Selectionmentioning
confidence: 99%